Intelligent Development Trend and Its Application in Housing in Johor, Malaysia - Goh, Alvin Wei Yang; Zainal, Rozlin; Abd Rahim, Mohd Hilmi Izwan; Mohd Noh, Hamidun (Research in Management of Technology and Business, 2024)
The global construction industry is increasingly embracing intelligent developments driven by emerging technologies, and Malaysia is actively participating in this trend by prioritizing smart cities and housing initiatives. Adoption of Intelligent Development (ID) technologies in the Malaysian construction industry faces challenges due to limited awareness, high costs, privacy concerns and unclear urbanization goals. Consequently, there are three objectives of the study carried out in this research which is to study the main ID practice in housing project trend, to identify the importance level of ID practice in housing project trend and to examine the strengthen relationship between the main ID practice with the main importance level of ID practice in housing project trend. This research focused on the housing project by developer companies around Johor Bahru as respondent. Total of housing project in Johor Bahru is 205, so the sample size is 136. The respondents were given a questionnaire by face-to-face meeting and in a link of google form through WhatsApp and Email. A total of 83 respondents (61%) had given feedback in the questionnaire. Frequency analysis was used to analyses the background of respondents while descriptive and crosstabs analysis was used to analyses the data for all objective. This research found that the main ID practice and importance level respectively sustainable design and increase security recorded as the highest frequency and importance. Meanwhile, the relationship between main practice and main importance level that strongest relationship is smart home system (SHSs) with reducing energy and lowering operational costs. Therefore, this study can help developers by emphasizing the main ID practice and main importance level of ID in housing project to enhance their housing projects. Leveraging the relationship framework for main practices with main importance level of ID provided by this study can give guideline to government and private housing developers work or cooperate closely together to adopt ID. While there are challenges to overcome, the potential long-term advantages make it a promising approach for future housing.